Penerapan Fisika Komputasi dengan MATLAB/Simulink pada Pemodelan Infeksi Wabah COVID-19 di Indonesia melalui Modifikasi Persamaan Differensial Bernoulli - Valentinus Galih Vidia Putra; Andrian Wijayono; Juliany Ningsih Mohamad; Irwan Irwan; Cahaya Rosyidan (Jurnal Teori dan Aplikasi Fisika, 2020)
The application of physics, in particular, the topic of differential equations is commonly used in mathematics, physics, engineering, and various other sciences to explain a phenomenon in a system, to produce a form of simulation and prediction of a fairly good mathematical equation is needed. This paper examines the use of MATLAB / Simulink to assist in modeling the solution of the differential equation problems by providing a case of mathematical modeling in the analysis of the COVID-19 plague in Indonesia in 2020 with the modification of the Bernoulli equation. In this study, it can be concluded that MATLAB / Simulink can be used to solve differential equation problems with Bernoulli's modification in the case of COVID-19 plague modeling quite accurately.